1989
DOI: 10.1080/03637758909390257
|View full text |Cite
|
Sign up to set email alerts
|

Test of an argumentative skill deficiency model of interspousal violence

Abstract: A model of interpersonal physical violence is derived from the aggression literature and then is utilized to investigate interspousal violence. The model posits that verbal aggression is a catalyst to violence when societal, personal, and situational factors are strong enough to produce a hostile predisposition. Unless aroused by verbal aggression, a hostile disposition remains latent in the form of unexpressed anger. The framework suggests that persons in violent, marriages are more verbally aggressive than o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
116
1
10

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(134 citation statements)
references
References 33 publications
7
116
1
10
Order By: Relevance
“…Research on verbal aggressiveness has shown that it damages the receiver's self-esteem, serves as a catalyst to interspousal violence (e.g., Gelles, 1974;Infante, Chandler, & Rudd, 1989), and results in less liking and lower credibility (Cole & McCroskey, 2003). Verbal aggressiveness predicts a variety of behaviors from alcohol consumption (see Graham, Schmidt, & Gillis, 1996;Moss & Kirisci, 1995) and video game use (see Anderson & Dill, 2000) to physical aggressiveness (e.g., Atkin,Smith,Roberto,Fediuk,76 K. Greene & M. Krcmar & Wagner, 2002) and substance use (Bukstein, 1996).…”
Section: Verbal Aggressiveness and Argumentativenessmentioning
confidence: 99%
“…Research on verbal aggressiveness has shown that it damages the receiver's self-esteem, serves as a catalyst to interspousal violence (e.g., Gelles, 1974;Infante, Chandler, & Rudd, 1989), and results in less liking and lower credibility (Cole & McCroskey, 2003). Verbal aggressiveness predicts a variety of behaviors from alcohol consumption (see Graham, Schmidt, & Gillis, 1996;Moss & Kirisci, 1995) and video game use (see Anderson & Dill, 2000) to physical aggressiveness (e.g., Atkin,Smith,Roberto,Fediuk,76 K. Greene & M. Krcmar & Wagner, 2002) and substance use (Bukstein, 1996).…”
Section: Verbal Aggressiveness and Argumentativenessmentioning
confidence: 99%
“…First, batterers may continue their psychological abuse after treatment (Adams, 1989;Edleson and Gruszinski, 1988;Hamberger and Hastings, 1988;Tolman and Bennett, 1990), perhaps to control emotional distance (Dutton and Browning, 1988) or because they. lack important skills (HoltzworthMunroe and Anglin, 1991;Infante et al, 1989;Morrison et al, 1987;Rosenbaum and Maiuro, 1990). Different patterns of verbal aggression (Gondolf and Fisher, 1988), one type of psychological abuse, and interaction (Christensen, 1987;Margolin et al, 1988) suggest different patterns of psychological abuse.…”
Section: Introductionmentioning
confidence: 97%
“…Often, items from the Conflict Tactics Scale (CTS; Straus, 1979) have been used (Barling et aL, 1987;Downs et aL, 1993;Edleson et al, 1991;Mason and Blankenship, 1987;Murphy and O'Leary, 1989;Stets, 1990). A notable exception is Infante et al (1989) who conceptualized verbal aggression broadly as attacks on the self-concept to inflict emotional pain.…”
Section: Introductionmentioning
confidence: 98%
“…(Waldo, 1987, p. 388) There are also ethical implications of skills interventions in interspousal violence, especially because the communication behavior usually preferred over verbal aggression is the use of argument. For example, Infante et al (1989) maintain that experimental research is needed to ascertain whether training in argumentative skills has predictable effects on verbal aggression that ultimately affect the level of physical aggression. experimental manipulation of argument and thus of verbal aggression raises the appalling possibility that experimentation would increase the risk of physical violence…”
mentioning
confidence: 97%